2018
DOI: 10.1105/tpc.17.00934
|View full text |Cite
|
Sign up to set email alerts
|

The m6A Reader ECT2 Controls Trichome Morphology by Affecting mRNA Stability in Arabidopsis

Abstract: The epitranscriptomic mark -methyladenosine (mA) can be written, read, and erased via the action of a complex network of proteins. mA binding proteins read mA marks and transduce their downstream regulatory effects by altering RNA metabolic processes. The characterization of mA readers is an essential prerequisite for understanding the roles of mA in plants, but the identities of mA readers have been unclear. Here, we characterized the YTH-domain family protein ECT2 as an mA reader whose mA binding function is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
393
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 286 publications
(428 citation statements)
references
References 67 publications
31
393
1
3
Order By: Relevance
“…Global RNA‐seq analyses of the model plant A. thaliana indicated the presence of m 6 A modifications within many nuclear‐encoded mRNA transcripts (Zhong et al , ; Bodi et al , ; Shen et al , ; Růžička et al , ; Wei et al , ; Parker et al , ). These analyses further suggested that the organellar (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Global RNA‐seq analyses of the model plant A. thaliana indicated the presence of m 6 A modifications within many nuclear‐encoded mRNA transcripts (Zhong et al , ; Bodi et al , ; Shen et al , ; Růžička et al , ; Wei et al , ; Parker et al , ). These analyses further suggested that the organellar (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…As in animals, the N 6 ‐methylation of adenosine residues in nuclear‐encoded mRNAs in land plants is positioned predominantly towards the 3′‐end of the transcript (Bodi et al , ; Dominissini et al , ; Chen and Liu, ; Luo et al , ; Ke et al , ; Wan et al , ; Burgess et al , ; Li et al , ; Scutenaire et al , ; Wei et al , ). This was also supported by Nanopore direct RNA sequencing of Arabidopsis plants (Parker et al , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants have more YTH domain proteins than other eukaryotes, including yeast, human and other mammals (Meyer and Jaffrey, ). For instance, 13 YTH domain proteins named ECT1‐12 and CPSF30 were found in Arabidopsis , which is significantly higher than that of the 5 YTH proteins identified in mammals (Meyer and Jaffrey, ; Wei et al ., ). The results showed that YTH proteins were widespread in land plants.…”
Section: Evolution Of M6a Methylation Components In the Plant Kingdommentioning
confidence: 97%
“…This modification regulates gene expression during a myriad of processes ranging from leaf and trichome development in Arabidopsis thaliana (Arribas-Hernández et al, 2018;Scutenaire et al, 2018;Wei et al, 2018) to cell fate determination in humans. These marks, which are deposited at specific mRNA sequences by m 6 A writers and removed by m 6 A erasers, recruit and anchor m 6 A-binding proteins (readers) that play vital roles in pre-mRNA splicing, mRNA degradation, and translation (reviewed in Meyer and Jaffrey, 2017).…”
mentioning
confidence: 99%